Polychlorinated Biphenyls Disrupt Blood–Brain Barrier Integrity and Promote Brain Metastasis Formation - Seelbach, Melissa (National Institute of Environmental Health Sciences, 2010)
BACKGROUND: Polychlorinated biphenyls (PCBs) comprise a ubiquitous class of toxic substances associated with carcinogenic and tumor-promoting effects as well as neurotoxic properties in the brain. However, the effects of PCBs on the development of tumor metastases are not fully understood. OBJECTIVE: We evaluated the hypothesis that exposure to individual PCB congeners can facilitate the development of brain metastases in immunocompetent mice via the disruption of the integrity of the blood–brain barrier (BBB). METHODS: C57/Bl6 mice were exposed to individual PCBs by oral gavage, and 48 hr later they were injected with luciferase-labeled K1735 M2 melanoma cells into the internal carotid artery. The development of metastatic nodules was monitored by bioluminescent imaging. In addition, we evaluated the functional permeability of the BBB by measuring permeability of sodium fluorescein across the brain microvessels. Expression and colocalization of tight junction (TJ) proteins were studied by Western blotting and immunofluorescence microscopy. RESULTS: Oral administration of coplanar PCB126, mono-ortho-substituted PCB118, and non-coplanar PCB153 (each at 150 μmol/kg body weight) differentially altered expression of the TJ proteins claudin-5, occludin, and zonula occludens-1 in brain capillaries. These alterations were associated with increased permeability of the BBB. Most importantly, exposure to individual PCB congeners enhanced the rate of formation and progression of brain metastases of luciferase-tagged melanoma cells. CONCLUSIONS: Our results show for the first time that exposure to individual PCBs can facilitate the formation of bloodborne metastases via alterations of the integrity of the brain capillary endothelium.